Metallicity distribution functions of the old populations of the magellanic clouds from RR Lyrae stars - Haschke, Raoul; Grebel, Eva K.; Duffau, Sonia; Jin, Shoko (The astronomical journal, 2012)
We present the ﬁrst metallicity distribution functions of the old ﬁeld populations in the Magellanic Clouds (MCs). Our metallicities are based on the Fourier decomposition of Type ab RR Lyrae light curves from the Optical Gravitational Lensing Experiment. On the metallicity scale of Zinn & West, we ﬁnd a mean metallicity of [Fe/H] = −1.50 ± 0.24 dex based on 16,776 RR Lyrae stars in the Large Magellanic Cloud (LMC). For the Small Magellanic Cloud (SMC) we obtain −1.70 ± 0.27 dex based on 1831 RR Lyrae stars. These uncertainties represent the intrinsic spread in the population rather than the standard deviation of the mean. Our results are in good agreement with the few existing spectroscopic metallicity determinations for LMC RR Lyrae stars from the literature. For both the LMC and the SMC the metallicity spread exceeds 1 dex in [Fe/H]. The distribution of metallicities in both Clouds is very uniform, and no signiﬁcant metallicity gradient is detectable. We also do not ﬁnd any pronounced populations of extremely metal-poor RR Lyrae candidates with metallicities well below −2 dex, although we need to caution that the photometric method used may overestimate the metallicities of metal-deﬁcient stars. Moreover, because of stellar evolutionary effects one does not expect to observe many RR Lyrae stars among very metal-poor horizontal branch stars. We suggest that the MCs experienced fairly rapid and efﬁcient early enrichment involving pre-enriched gas as well as possibly gas infall, while metal loss through outﬂows does not seem to have played a signiﬁcant role. Moreover, we suggest that the differences in the metallicities of the old population of LMC and SMC make an origin from a single, common progenitor unlikely, unless the separation happened very early on.